PEMBENTUKAN NOMINA MELALUI AFIKSASI DALAM BAHASA MELAYU RIAU DIALEK TANJUNG MEDAN KECAMATAN TANJUNG MEDAN KABUPATEN ROKAN HILIR - Dedi Syahputra; Hasnah Faizah; Nursal Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research entitled Formation of Nomina In Riau Malay Language Dialect Tanjung Medan District Tanjung Medan Rokan Hilir Regency. This study aims to find answers to the problems that have been described in the previous section, which describes the process of formation of nouns through affixasi contained in the Riau Malay dialect Medan. The method used is descriptive analysis method with qualitative approach. the data in this study are data obtained from native speakers of Riau Malay dialect of Medan, Tanjung Medan, Rokan Hilir Regency, which is about noun berated and which is in the form of iteration. The result of the research was found (1) Nomina Derivation Prefix amounted to 27 data, (2) Infomation Derivation Nomina amounted to 20 data, (3) Suffix Derivation Nomina amounted to 26 data, (4) Conversion Derived Nomina 27 data. Keywords : Noun formation, affixation, riau malay language, dialect tanjung medan, tanjung medan sub district, rokan hilir district